Analisis Sistem Jaringan Tata Air Pada Lahan Rawa Pasang Surut, Desa Telang Karya, P87S, Banyuasin, Sumatera Selatan - Ma'shum, Halim (Universitas Tanjungpura, 2024)
The world's growing population is increasing the need for land, prompting the conversion of productive agricultural land into non-agricultural purposes. This has led to a shift in agricultural development to sub-optimal lands, such as tidal swamplands. However, several problems arise along the way, including water management. A good water management network is necessary for supporting efficient water use. This study aims to analyze the water system network on tidal swamps to support agricultural activities. The survey and field observation methods were used to collect data. The results showed that the water system in Telang Karya Village, P87S, Banyuasin, South Sumatra, experienced sedimentation in the tertiary channel. In channel 3, the thickness of sediment reached 72 cm, resulting in silting, which reduces water discharge. Field observations revealed that sedimentation occurs due to the channels being overgrown by wild plants. This hampers the water flow, causing it to slow down or even stop. In some tertiary channels, the watergate operation needs to be carried out optimally. Maintaining the ideal conditions of tertiary channels is crucial, and watergate operations should be performed based on the needs of the plants.